Thai men's experiences of alcohol addiction and treatment - Kulnaree Hanpatchaiyakul; Henrik Eriksson; Jureerat Kijsompon; Gunnel Östlund (Taylor & Francis Group, 2014)
Background: Men are overrepresented with regard to alcohol addiction and in terms of alcohol treatment worldwide. In Thailand, alcohol consumption continues to rise, but few of those afflicted with alcohol addiction attend alcohol treatment programs, even though there is universal care for all. No comprehensive studies have been done on men's experiences with addiction and alcohol treatment programs in Thailand. Objective: The aim of this study was to explore men's experiences in terms of the 'pros and cons of alcohol consumption' in order to identify the barriers that exist for Thai men with regard to alcohol addiction and the decision to stop drinking. Design: Purposive sampling was applied in the process of recruiting participants at an alcohol clinic in a hospital in Thailand. Thirteen men with alcohol addiction (aged 32-49 years) were willing to participate and were interviewed in thematic interviews. The analysis of the data was done with descriptive phenomenology. Results: Through men's descriptions, three clusters of experiences were found that were 'mending the body', 'drinking as payoff and doping related to work', and 'alcohol becoming a best friend' as ways of describing the development of addiction. Conclusions: The results highlight the importance of addressing concepts of masculinity and related hegemonic ideas in order to decrease the influence of the barriers that exist for Thai men with alcohol addiction with regard to entering treatment and to stop drinking.